KORUPSI DALAM PERSFEKTIF FILSAFAT HUKUM ISLAM - Firmansyah, Firmansyah (Al-Amwal : Journal of Islamic Economic Law, 2016)
Acts of corruption is the act Dirty, cheating and bad Judging from the positive law and legal From the legal perspective Islam faktor causes of corruption there are prayer external (opportunities , Needs ) and internal AS namely greed And its reduced intelligence spiritual (religious problem ) or word heart identifiable or in objectivation From prayer.for the future setting on the problem of corruption should be accommodated religious hearts by making anti - corruption jurisprudence, order Becoming Guidelines and Reference and Rules paled not animates positive Yang was born and penalization Right to review Performers Corruptor for the benefit considerations